Comparison of theoretical and experimental microhardness of tetrahedral binary Zn1-xErxO semiconductor polycrystalline nanoparticles - Asikuzun, E.; Ozturk, O. (Elsevier BV, 2019)
Abstract Zn 1 − x Er x O polycrystalline nanoparticles with various compositions ( x = 0.01 , 0.02 , 0.03 , 0.04 , 0.05 , and 0.10 ) were prepared using sol–gel techniques, for which zinc acetate dihydrate and erbium 2–4 pentanedionate are used as precursors. Nanoparticles were pressed under a pressure of 4  tons for 5  min into disk-shaped compacts with 2 mm thicknesses and 10 mm diameters. The pressed samples were annealed at 400 °C for 30  min. X-ray diffraction (XRD), scanning electron microscopy (SEM), and Vickers microhardness analyses of the produced Er-doped ZnO bulk nanomaterials were performed. Specifically, in this study we focused on the analysis of their mechanical properties. Undoped and Er-doped bulk samples were investigated according to Meyer's law; the proportional sample resistance (PSR), elastic/plastic deformation (EPD), and indentation-induced cracking (IIC) models; and the Hays–Kendal (HK) approach. As a result, the IIC model was more suitable to determine the micromechanical properties and the reverse indentation size effect ( R ISE ) behavior of Er-doped ZnO semiconductors.